Vitamin C-Induced Oxalate Nephropathy in a Septic Patient. (26th April 2021) - Wissanji, Tasheen; Dupuis, Marie-Eve; Royal, Virginie; Pichette, Vincent; Wang, Han Ting
Abstract : OBJECTIVES: Vitamin C is a novel treatment currently under investigation in the management of sepsis. Adverse renal effects of vitamin C through hyperoxaluria have been described in the past. DATA SOURCES: We report the case of a 63-year-old man admitted in a community-based hospital with a diagnosis of sepsis of pulmonary origin. DATA EXTRACTION: On day 19, despite a having developed oligoanuric acute kidney injury, a regimen of IV vitamin C, hydrocortisone, and thiamine was undertaken for 4 days. On day 23, the patient required renal replacement therapy with an estimated glomerular filtration rate of 7 mL/min. Renal biopsy revealed extensive acute tubular necrosis associated with the presence of intratubular crystal of calcium oxalate. Conclusion: Although vitamin C seems to be a possible therapeutic asset in the supportive care of sepsis patients, larger cohorts are required to ensure its safety and underlying or novel kidney injury should forewarn clinicians as to its use.